The Spinning of the Wheels: Women’s Travel Stories in Latin Funerary Inscriptions - Foubert, Lien (Gerión. Revista de Historia Antigua, 2020)
This contribution examines Latin funerary inscriptions in which the movements of middle-class women within and beyond the Italian peninsula constitute the focus point of the text. It aims to shed light on how these texts relate to other social discourses, such as those centred on class and gender. Travel is by default a disruptive activity as it took women out of the household and into the public world. When a commemorator made the deliberate choice to include a reference to a woman’s journey, he or she must have been well aware of the fact that such an inclusion deviated from the canonical description of a woman as an ideal matrona. In this article, I will argue that this awareness and the desire to conform to the dominant ideological discourses of their time led to the embedment of these small travel accounts in a broader discourse of ideal female conduct.